The Black and White of GoFood Co-Branding - Palguna, I Gusti Ngurah Bagus Dwira (Jurnal Entrepreneur dan Entrepreneurship, 2020)
Abstract This research aims to find out how the implementation of Gofood co-branding with its culinary partners, as well as to find out the pros and cons felt by partners since carrying out their co-branding with Gofood. This research is a qualitative research. The focus is on informants’ personal, not specific companies or agencies, understanding. The data collection technique used is in-depth interviews with source triangulation as a data validity technique. The results obtained show that Gofood's co-branding with restaurant partners falls into the same type of co-branding but with different levels of co-branding and value creation. The pros felt by the partners lies in increasing sales, brand awareness and coverage of the sales areas while the thing that is a contra is pricing. Keywords--- co-branding, third-party online food delivery, business owner experience, Gofood